A comprehensive assessment of alternative absorber-exchanger designs for hybrid PVT-water collectors - Herrando,Zapater M; Ramos,Cabal A; Zabalza,I; Markides,C (Applied Energy, 2019)
In this paper, 26 alternative absorber-exchanger designs for hybrid PV-Thermal (PVT) solar collectors are proposed and compared against a reference-case, commercial sheet-and-tube PVT collector. The collectors involve different geometric design features based on the conventional sheet-and-tube configuration, and also on a newer flat-box structure constructed from alternative polymeric materials with the aim of maintaining or even improving heat transfer and overall (thermal and electrical) performance while achieving reductions in the overall weight and cost of the collectors. The main contributions of this research include: (i) the development and validation of a detailed 3-D computational finite-element model of the proposed PVT collector designs involving multi-physics processes (heat transfer, fluid dynamics and solid mechanics); (ii) results from comparative techno-economic analyses of the proposed PVT designs; and, (iii) further insights from thermal stress and structural deformation analyses of the proposed collectors, which are crucial for ensuring long lifetimes and especially important in the case of polymeric collectors. The results show that, in general, the flat-box designs (characterised by a thin absorber plate) are not sensitive to the flow-channel size or construction material, at least within the range of investigation. A PVT collector featuring a polycarbonate (PC) flat-box design with 3×2mm rectangular channels appears to be a particularly promising alternative to commercial PVT collectors, achieving a slightly improved thermal performance compared to the reference case (with a 4% higher optical efficiency and 15% lower linear heat-loss coefficient), while also lowering the weight (by around 9%) and investment cost (by about 21%) of the collector. The structural analysis shows that the maximum von Mises stress experienced in the absorber-exchanger of the PC flat-box collector is considerably lower than that in the copper sheet-and-tube c